The adoption of new knowledge as the factor of international competitiveness - Antevski Miroslav (Međunarodni Problemi)
This paper deals with the problem of adoption of new knowledge as the core factor of development and international competitiveness. Differences between countries in the level of GDP are largely caused by differences in the levels of technological development and the degree of productivity. R&D sectors and innovative activity are emerging as the key determinants of productivity growth and thus the international competitiveness of nations. The international diffusion of knowledge is an important contributor to the innovation in the national country. Different channels of knowledge diffusion have a different developmental potentials for the host country. FDI and TNCs investment are considered to be a large potential source of new technology and knowledge for host countries. The more technologies brought in the host country, the larger is the scope for technology and knowledge spillovers. Such effects may be significant, but they depend to a large extent on host countries' ability to accept and adopt available technologies and knowledge. If the technology gap between countries is too large, then the spillovers may not materialize.